Multisectoral action towards sustainable development goal 3.d and building health systems resilience during and beyond COVID-19: Findings from an INTOSAI development initiative and World Health Organization collaboration - Hellevik, Siri; Mustafa, Saqif; Zhang, Yu; Shirsat, Archana; Saikat, Sohel (Frontiers in Public Health, 2023)
As the world was facing a global health crisis, the immense relevance of strong and resilient public health systems, the importance of an integrated approach, the widening of inequalities during such pandemics and fears of vulnerable sections being left behind were and remain issues that require Supreme Audit Institutions (SAIs) enquiry as independent public oversight bodies. As SAIs provide independent external oversight and contribute to follow up and review of national targets linked to the Sustainable Development Goals (SDGs) in their respective countries, they can play an important role in national recovery efforts. WHO and INTOSAI Development Initiative (IDI) have been collaborating in facilitating SAIs’ audits of strong and resilient national public health systems linked to the national target of SDG 3.d in 40 countries across Africa, Americas, Asia and Oceania between 2021 and 2022. This paper aims to convey key lessons learned from the joint multisectoral collaboration that can contribute to building health systems resilience in ongoing recovery efforts. WHO’s Health Systems Resilience team has supported IDI and SAIs by delivering training and reviewing SAIs' work from a health systems resilience perspective. IDI has provided the technical expertise on performance audits. The audits are expected to highlight current capacities of health systems resilience; the extent to which a whole-of-government approach and policy coherence have been utilised; and government efforts related to multistakeholder engagement and leaving no one behind in building health systems resilience related to progressing towards achieving the national target linked to 3.d by 2030. the collaboration shows that undertaking a complex health audit in the middle of a pandemic is possible and can contribute to building health systems resilience and recovery efforts. This collaboration also demonstrates key considerations needed for successful partnership across multisectoral partners at global, regional and national levels, Such considerations can be applied in different contexts to ensure whole-of-government action in building health systems resilience and monitoring and evaluation to maintain and accelerate progress towards SDG3.d, health security and universal health coverage (UHC).